Effect of seasonal variations on some nutritional and physiological parameters of Egyptian sheep - ABDEL-BAKI, S M; MEKKAWAY, M Y; HASSONA, E M; NOWAR, M S; BASSUNY, S M; IBRAHEEM, S A (The Indian Journal of Animal Sciences, 2013)
The effect of seasonal variations on feed and water consumption. nutrients digestibility. nutritive value, N-balance. certain ruminal and physiological parameters and thyroid activity ware studied in Egyptain sheep. Two feeding groups were designed, In each group 4 metabolism trials (1 trial in each season) were carried out using 3 fistulated local rams. Rams of group 1 were fed restricted ration (RFG) containing 65% concentrate mixture and 35% wheat straw to cover their maintenance requirements of DCP and SE. Rams of group 2 were fed the same concentrate mixlure 10 cover their maintenance requirements of DCP. Wheat straw was offered ad lib. (AFG).Intake of ration and wheat maw was not significantly affected by seasonal variations in RFG. The same trend was observed for ralion intake in AFG. but whent straw intake was significantly highest in spring and winter. The microbial protein synthesis was significanlly lowest in summer than in other seasons in the 2 groups. This was accompanied by an increase in mminal ammonia-No Thyroid hormones (T3 and T4) Concentrations were significantly highest in autumn and the lowest in summer in RFG group. The same trend was observed in AFG without significant differences in T4 concentrations. The digestibility lind nutritive values or TDN, SE and DCP were highest in Summer, and they were lowest in spring in RFG group. Daily feed units intake and N-balance per kg W075 were not significantly affected by seasonal variations. The same trend was observed for numen and rectal temperature and pulse rate. Skin temperature and respiration rate Were significantly higher in slimmer than in other seasons of both the groups.